Determinants of the attractiveness of telework before the outbreak of the COVID-19 pandemic - Walentek, Dorota (Determinanty atrakcyjności wykonywania telepracy w przeddzień wybuchu pandemii COVID-19, 2020)
Telework, also known as remote work, is now an increasingly popular work system in Poland and around the world. However, the reasons for undertaking remote work by individual teleworkers may be different. The article contains a literature review in terms of both the explication of the concept of teleworking and the motives for undertaking it. The results of the author’s study were also presented, the aim of which was to identify the most important factors influencing the interest in teleworking among students. It was shown that the main motivating factors to work remotely are flexible working hours, the ability to work anywhere in the world and independent work organization. The study was a pilot study carried out just before the COVID-19 pandemic, which forced the introduction of remote work in many organizations that had not used teleworking so far. The intention of the author is to conduct a similar study every one to two years in order to compare the main motives for undertaking remote work before and during the pandemic, or just after its completion
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 1 (55), s. 80-95
Keywords: telework; remote work; determinants of undertaking; COVID-19; telepraca; praca zdalna; determinanty podejmowania telepracy; pandemia COVID-19